Characteristics of fuel oil from the Krapivinskoe field (Part 1) - Tatyana V. Cheshkova; Татyana А. Sagachenko; Kirill A. Cherednichenko; Alexandra S. Vishnevich; Raisa S. Min (Известия Томского политехнического университета: Инжиниринг георесурсов)
Relevance. The need to obtain information about the chemical nature of the resin-asphaltene and oil components of atmospheric residue from distillation of crude oil produced at the Krapivinskoe field in order to select optimal technologies for its rational utilization. Aim. To study the structures of asphaltene macromolecules and resin substances and the molecular composition of the oil components of atmospheric residue from distillation of crude oil produced at the Krapivinskoe field. Methods. Transmission electron microscopy, X-ray phase analysis, IR spectroscopy, 1H NMR spectroscopy, structural group analysis, chemical destruction, gas chromatography-mass spectrometry. Results. The structure of resin-asphaltene substances and the molecular composition of atmospheric residue obtained in the course of atmospheric distillation of oil from the Krapivinskoe field in laboratory conditions have been characterized using a complex of physicochemical research methods. It was found out that asphaltenes of atmospheric residue have a predominantly amorphous structure because of the presence of a developed alkyl chain configuration in their macromolecules. Mean asphaltene molecules consist of three structural blocks, which basis is triarene cores condensed with four to five naphthenic rings. These naphthenoaromatic systems neighbor upon methyl substituents only. The mean molecules of atmospheric residue resins are predominantly single-block. Their structural blocks are more compact due to the smaller number of aromatic and naphthenic rings in the naphthenoaromatic system. A feature of mean resin molecules is also the presence of relatively long alkyl substituents in the blocks. It was established that the structure of asphaltenes and atmospheric residue resins contains fragments linked to each other or to the naphthenoaromatic core of their macromolecules through sulfide and ether bridges. In both types of ‘linked’ fragments, n-alkanes, n-alkylcyclohexanes and hopanes were identified. Among the fragments linked through sulfide bridges, n-alkylbenzenes, n-alkylmethylbenzenes and n-alkanoic acids were additionally identified, while ethyl esters of n-alkanoic acids were identified among fragments linked through ether bridges. A structural feature of the atmospheric residue resins is the presence of phenylalkanes with different positions of the phenyl substituent in both types of bridge-linked compounds. Steranes and phenanthrenes are present in the composition of compounds linked through sulfide bridges. The oil components of atmospheric residue contain n-alkanes, n-alkylcyclohexanes, hopanes, steranes, n-alkylbenzenes, n-alkylmethylbenzenes, alkylnaphthalenes and alkylphenanthrenes.